2020
DOI: 10.31730/osf.io/q8k5w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical learning in children's emergent L2 literacy: Cross-cultural insights from rural Côte d'Ivoire

Abstract: Children around the world learn to read across radically different educational systems and communities. In the west African nation of Côte d’Ivoire, children enter the fifth grade (CM-1) with widely varying literacy skills in French, the official language for primary education. Previous studies have often linked performance in statistical learning tasks with differences in children’s and adults’ literacy outcomes, mainly in Western and high-income educational contexts. We asked whether Ivorian children’s indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…This approach of measuring online learning has been validated in our previous work in adult learners: their responses to target stimuli accelerated more quickly in structured sequences, similar to the ones used here, than in random sequences where no triplets were formed and the same stimuli were displayed in a random order (Schneider et al, 2020;Tang et al, 2022). Significant RT acceleration was also observed in children using a tablet to respond to targets in the third position, but not the first position, of a triplet, indicating that they had learned the triplet structure and could anticipate the target (Zinszer et al, 2020).…”
Section: Statistical Learning (Sl)mentioning
confidence: 53%
“…This approach of measuring online learning has been validated in our previous work in adult learners: their responses to target stimuli accelerated more quickly in structured sequences, similar to the ones used here, than in random sequences where no triplets were formed and the same stimuli were displayed in a random order (Schneider et al, 2020;Tang et al, 2022). Significant RT acceleration was also observed in children using a tablet to respond to targets in the third position, but not the first position, of a triplet, indicating that they had learned the triplet structure and could anticipate the target (Zinszer et al, 2020).…”
Section: Statistical Learning (Sl)mentioning
confidence: 53%
“…We asked whether previously reported correlations between non-linguistic statistical learning (SL) and children's literacy existed for children in southeastern Côte d'Ivoire learning to read in their second language. Following extensive pilot research reported by Zinszer et al (2022) and in the supplemental materials, we proposed a set of adaptations to existing visual and auditory SL tasks to measure individual differences among children who (1) have no experience using personal computers, (2) are unaccustomed to repetitive forced-choice test designs, and (3) are located in rural communities with limited access to typical laboratory infrastructure. Our results provided moderate to strong evidence against direct correlations (outside the interval [-0.20, 0.20]) between SL and L2 literacy, but we identified relationships between French phonological awareness and visual SL and between French phonological awareness and L2 literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-seven children completed an auditory statistical learning task (ASL) using auditory pure tones, and 46 completed a visual statistical learning task (VSL) using cartoon aliens. The VSL data tasks were also reported by Zinszer et al (2022), but that paper used linear mixed-effects models while this analysis closely follows the data processing and analysis steps described by Qi et al (2019) for better comparison. Table 2 summarizes the experiment parameters.…”
Section: Pilot Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Note that some studies used adaptions of this test in languages other than English. Zinszer et al (2020) adopted the Woodcock–Johnson-III Test of Cognitive Abilities (Woodcock et al, 2001) to assess children’s vocabulary knowledge of native language (Attié) and their second language (French). Shafto et al (2012) asked parents to fill out the MacArthur–Bates Communicative Development Inventory (Fenson et al, 2006) to learn about infants’ vocabulary knowledge.…”
Section: Methodsmentioning
confidence: 99%